Antipsychotic medications for older adults with delirium admitted to hospital - Reppas-Rindlisbacher, Christina; Stall, Nathan M.; Wiesenfeld, Lesley (Canadian Medical Association journal (CMAJ), 2023)
Antipsychotic medications are commonly used in hospitals to manage patients with delirium, which affects a significant percentage of older adults admitted to the hospital. However, these medications should not be used as standard treatment for delirium. Instead, delirium management should focus on addressing underlying causes, optimizing environmental factors, and implementing nonpharmacologic interventions. A systematic review found no difference between antipsychotic medications and placebo in terms of delirium duration, severity, length of hospital stay, or mortality. However, most studies did not differentiate between hypoactive and hyperactive delirium or examine the impact of antipsychotic medications on patient and family experience. Antipsychotic medications may be considered for patients with delirium experiencing severe agitation or distress, or for those at risk of self-harm, harming others, or compromising essential medical therapy. They are preferred over benzodiazepines, except for specific indications such as delirium associated with alcohol or benzodiazepine withdrawal. However, they should not be used for hypoactive delirium. Before using antipsychotic medications, it is important to assess the individual risks and benefits, as these medications can have serious adverse effects such as sedation, hypotension, falls, parkinsonism, QT interval prolongation, and aspiration pneumonia. Frequent reassessment of treatment is necessary to determine if dose reduction or discontinuation is appropriate. Many patients are discharged from the hospital on antipsychotic medications without a clear indication for ongoing treatment. Therefore, these medications should be prescribed at the lowest effective dose for the shortest possible duration and patients should be re-evaluated shortly after discharge.